Pengaruh Jumlah Inang Chilo sacchariphagus Boj. (Lepidoptera: Crambidae) dan Nisbah Kelamin Cotesia flavipes Cam. (Hymenoptera: Braconidae) terhadap Keturunan yang Dihasilkan di Laboratorium - Rosma Susiwaty Situmeang; Maryani Cyccu Tobing*; Mukhtar Iskandar Pinem (Jurnal Agroekoteknologi, 2014)
The objectives of the research were to study the effect of the number host C. sacchariphagus andsex ratio of C. flavipes on the progeny produced. The research was held at the Laboratory ofSugarcane Research and Development Sei Semayang, Binjai, Medan, North Sumatera from Julyuntil September 2013. This method used Randomized Complete Design Factorial with two factors.The first factor was sex ratio of C. flavipes (1 male:1 female, 1 male:2 females, 1 male:3 females, 2males:2 females, 2 males:3 females) and the second factor was number of C. sacchariphagus (5 and10 larvae) with three replications. The results showed that the number of larvae ofC. sacchariphagus and sex ratio of C. flavipes significantly effected on the sex ratio of progenyproduced. The highest percentage (58.67%) of the number of host C. sacchariphaguon 5 larvae andthe lowest (36.00%) on 10 larvae. The highest sex ratio (1:2.5) on 1 male:1 female and lowest(1:0.6) on 2 males:3 females. Average male and female of sex ratio is 1: 1.54.Key words : C. flavipes, C. sacchariphagus, parasitism, sex ratio,.